A functional pseudogene, NMRAL2P, is regulated by Nrf2 and serves as a coactivator of NQO1 in sulforaphane‐treated colon cancer cells. Issue 4 (3rd January 2017) - Johnson, Gavin S.; Li, Jia; Beaver, Laura M.; Dashwood, W. Mohaiza; Sun, Deqiang; Rajendran, Praveen; Williams, David E.; Ho, Emily; Dashwood, Roderick H.
Abstract : NmrA‐like redox sensor 2 ( NMRAL2P ) is a novel functional pseudogene, the first to be identified both as a direct transcriptional target of Nrf2, and as a downstream coregulator of Nrf2‐dependent gene activation in response to sulforaphane treatment. Abstract : Scope: The anticancer agent sulforaphane (SFN) acts via multiple mechanisms to modulate gene expression, including the induction of nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2)‐dependent signaling and the inhibition of histone deacetylase activity. Transcriptomics studies were performed in SFN‐treated human colon cancer cells and in nontransformed colonic epithelial cells in order to pursue new mechanistic leads. Methods and results: RNA‐sequencing corroborated the expected changes in cancer‐related pathways after SFN treatment. In addition to NAD(P)H quinone dehydrogenase 1 ( NQO1 ) and other well‐known Nrf2‐dependent targets, SFN strongly induced the expression of Loc344887 . This noncoding RNA was confirmed as a novel functional pseudogene for NmrA‐like redox sensor 1, and was given the name NmrA‐like redox sensor 2 pseudogene ( NMRAL2P ). Chromatin immunoprecipitation experiments corroborated the presence of Nrf2 interactions on the NMRAL2P genomic region, and interestingly, NMRAL2P also served as a coregulator of NQO1 in human colon cancer cells. Silencing of NMRAL2P via CRISPR/Cas9 genome‐editing protected against SFN‐mediated inhibition of cancer cell growth, colony formation, and migration. Conclusion: NMRAL2P is the first functional pseudogene to be identified both as a direct transcriptional target of Nrf2, and as a downstream regulator of Nrf2‐dependent NQO1 induction. Further studies are warranted on NMRAL2P ‐Nrf2 crosstalk and the associated mechanisms of gene regulation.